TINGKAT KREATIVITAS SLOW LEARNERS DALAM MEMECAHKAN MASALAH MATEMATIKA - Rima Aksen Cahdriyana; Rahayu Setyorini (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The heterogeneity of students in Indonesia is a challenge for teachers today. Creativity is not only for students with high mathematical abilities, but also introduced to students who are in the slow learner category. This research is a qualitative descriptive study that aims to describe the level of creativity of the slow learner, and to describe how to develop creative thinking skills for slow learners. The subjects in this study from one of the schools in Yogyakarta whose students were included in the slow learner category. The subjects were selected by purposive sampling. Data collection had been done by giving problems solving to subjects, then interviewing them to clarify the answers that have been written. Data analysis had been stopped on the third subject because the data from the third subject was no difference with data from the previous subject. The results of this study indicate that slow learners are not able to show the three indicators of creativity in solving mathematical problems (fluency, flexibility, and novelty), so that the slow learners are classified as creative thinking skills level 0 or included in not creative students. Other findings indicate that one subject indicated being able to show one indicator of creativity, namely fluency, so that subject classified as level 1 (almost not creative).